PEMBUATAN DESAIN DAN PEMBUATAN PRODUK FURNITUR SEBAGAI PENUNJANG AKTIVITAS BAGI PENYANDANG DISABILITAS FISIK - Made Anggita Wahyudi Linggasani; I Dewa Ayu Eka Pertiwi; I Wayan Yogik Adnyana Putra; Gde Bagus Andhika Wicaksana (Jurnal Abdi Masyarakat, 2025)
The Special Education Foundation (YPK) has been committed since 2001 to filling the gap in health and rehabilitation services for people with disabilities in Bali. Through the development of its services, YPK not only focuses on physical and psychological health aspects but also expands its scope into education as part of efforts to create a more inclusive environment for people with disabilities. In facing challenges in providing facilities and equipment to support rehabilitation activities—particularly the need for specially designed furniture—YPK recognizes the importance of collaboration with academia, especially with Warmadewa University. This community service activity focuses on the significance of such collaboration in developing ergonomic, accessible, and aesthetic furniture design solutions. Special furniture such as walkers, support chairs, and support tables play a vital role in fostering independence and improving the quality of life of YPK service recipients. Through this collaboration, it is expected that innovations in furniture design will emerge that not only meet functional needs but also take into account ergonomic and aesthetic aspects, in line with the principles of inclusive education. This community service activity explores how academic insights in design and ergonomics can make significant contributions to creating sustainable and effective solutions, reinforcing the importance of cooperation between the non-profit and academic sectors in addressing social challenges. The outcomes of this collaboration are expected not only to strengthen the supporting infrastructure at YPK but also to serve as a model for similar initiatives focusing on disability community services.